Burkina Faso : Strategy for Accelerated Growth and Sustainable Development 2011-2015. (IMF Staff Country Reports; Country Report, 2012)
This paper focuses on the Strategy for Accelerated Growth and Sustainable Development (SCADD) for Burkina Faso. It provides an overview of a decade of development, takes stock of the recent performance of Burkina Faso in various areas, and identifies the main challenges. The paper spells out a direction for the SCADD for 2011-15, by ensuring that its vision is based on sector priorities to achieve set objectives. The risks that could impede the success of the development scheme desired by the government are also discussed.